Some common fixed point theorem of rational contractive mappings in dislocated metric spaces - Jeevanandam Uma Maheswari; Annadurai Anbarasan; Mani Gunaseelan; Kumar Santosh (Topological Algebra and its Applications, 2023)
We improve the rational contractive condition and prove the common fixed point in the dislocated metric spaces. In addition, the new generalized rational contraction has existence of a common solution for a system of integral equations.